The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.18632/oncotarget.15520
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic role of microRNA-34a in breast cancer: a systematic review and meta-analysis

Abstract: BackgroundMicroRNA-34a (miR-34a) is a master regulator of tumor suppression in breast cancer (BC). This systematic review aims to analyze the diagnostic accuracy of miR-34a in the detection of BC as a biomarker.ResultsA total of 1858 BC cases and 494 controls from thirteen eligible studies reported in 9 publications were included. The overall pooled sensitivity, specificity, negative likelihood ratio (NLR), positive likelihood ratio (PLR), and diagnostic odds ratio (DOR) were 85.50% (95% CI: 83.80-87.00%), 70.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 53 publications
3
44
1
1
Order By: Relevance
“…miR‐34a, regarded as a tumor suppressor, is decreased in breast cancer cell lines and tissues . In the current study, we detected that the level of miR‐34a was decreased in breast and tumor tissues in MNU‐treated rats, and that delphinidin treatment effectively upregulated the level of miR‐34a in tumor tissues.…”
Section: Discussionsupporting
confidence: 51%
“…miR‐34a, regarded as a tumor suppressor, is decreased in breast cancer cell lines and tissues . In the current study, we detected that the level of miR‐34a was decreased in breast and tumor tissues in MNU‐treated rats, and that delphinidin treatment effectively upregulated the level of miR‐34a in tumor tissues.…”
Section: Discussionsupporting
confidence: 51%
“…In this study, we found that miR-34a expression was significantly lower in TNBC cells compared with normal breast epithelium and that this lower expression was significantly associated with shorter overall patient survival, indicating that miR-34a is a prognostic factor in patients with TNBC. In addition, Imani and colleagues showed that miR-34a inhibits TWIST1, ZEB1, and NOTCH1 expression through binding to their 3 0 -UTR and reduces the metastatic and invasive features of metastatic breast cancer (34,35). The TP53 gene (encoding the p53 protein), which is mutated in about 50% of human cancers and 84% of TNBC tumors (36), was shown to induce miR-34, which turned out to be direct p53 target genes (37).…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNA-34a has attracted interest recently because of its ability to modulate a myriad of oncogenic functions in different cancers [21][22][23][24][25][26][27]. Not only does it play a role in cancer metastasis [28,29] and drug resistance [30], it is now being evaluated as a diagnostic as well as a prognostic biomarker [31][32][33]. In addition, a miR-34a inhibitor has been identified that may effectively protect against sevoflurane-induced hippocampal apoptosis by targeting Wnt1 and activating the Wnt/β-catenin pathway [34].…”
Section: Introductionmentioning
confidence: 99%